2017
DOI: 10.1371/journal.pone.0170354
|View full text |Cite
|
Sign up to set email alerts
|

Clonal and serotype dynamics of serogroup 6 isolates causing invasive pneumococcal disease in Portugal: 1999-2012

Abstract: Although serogroup 6 was among the first to be recognized among Streptococcus pneumoniae, several new serotypes were identified since the introduction of pneumococcal conjugate vaccines (PCVs). A decrease of the 6B-2 variant among invasive pneumococcal disease (IPD), but not 6B-1, was noted post conjugate vaccine introduction, underpinned by a decrease of CC273 isolates. Serotype 6C was associated with adult IPD and increased in this age group representing two lineages (CC315 and CC395), while the same lineage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Only two clinical cases of adults with IPD caused by 6C pneumococci were recorded. Low prevalence of serotype 6C IPD in children has also been observed in other studies from France, Portugal, and Brazil [22][23][24]. There are also investigations in which 6C is becoming more common as a causative agent of IPD, which confirms that vaccination is accompanied with serotype dynamics and rise in the frequency of NVTs [25][26][27].…”
Section: Discussionsupporting
confidence: 69%
“…Only two clinical cases of adults with IPD caused by 6C pneumococci were recorded. Low prevalence of serotype 6C IPD in children has also been observed in other studies from France, Portugal, and Brazil [22][23][24]. There are also investigations in which 6C is becoming more common as a causative agent of IPD, which confirms that vaccination is accompanied with serotype dynamics and rise in the frequency of NVTs [25][26][27].…”
Section: Discussionsupporting
confidence: 69%
“…Keywords: Central nervous system infections, North China, Pathogens distribution, Antibiotic susceptibility, Risk factors Definitions CNS infections was diagnosed according to the definitions of Centers for Disease Control and Prevention (CDC) as follows [17]: (1) isolation of pathogens from CSF; (2) patient was considered at least one of the following signs with no other recognized cause: fever (> 38 °C), headache, stiff neck, meningeal signs, cranial nerve signs, changing level of consciousness, or confusion; (3) increased white cells, elevated protein, and/or decreased glucose in CSF. MDR is defined as non-susceptibility to three or more classes of antibiotics, and extensively drugresistant (XDR) is defined as non-susceptibility to at least one agent in all but two or fewer antimicrobial categories [18,19]. The study population was divided into two groups respectively according to whether the patients survived and whether the patients detected with MDR bacteria in the CSF.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented suggest that the use of conjugate vaccines with a higher valence than PCV10, licensed (PCV13, PCV15, or PCV20) or under development (PCV24), would increase protection against IPD in both of the studied populations, given that their formulation includes serotypes 19A and 3, the most prevalent serotypes in Brazil. Studies have demonstrated the presence of cross-protection between serotype 6A, an antigen present in vaccine formulations other than PCV10, and serotype 6C [ 33 , 34 , 35 , 36 ]. Serotype 6C was the third most prevalent serotype in Brazil described in this study, so a potential expansion in IPD protection could be obtained with the introduction of vaccines which include serotype 6A.…”
Section: Discussionmentioning
confidence: 99%